The impact of voice assistants on consumer intention to use self-driving cars - Bilro, R. G.; Custódio, C. M. (Proceedings of Academy of Marketing 2023 Annual Conference and Doctoral Colloquium: From Revolution to Revolutions, 2023)
This study examines the influence of voice assistants’ attributes on consumer intention to use self- driving cars and WOM intentions. Results indicate that a positive attitude toward voice assistant attributes positively impacts the intention to use self-driving cars. The study suggests that integrating voice assistants in self-driving cars can increase consumer adoption.